Efficacy of Liming Forest Soil in the Context of African Swine Fever Virus - Franziska Tanneberger; Ahmed Abd El Wahed; Melina Fischer; Paul Deutschmann; Hanna Roszyk; Tessa Carrau; Sandra Blome; Uwe Truyen (Viruses, 2022)
Since September 2020, Germany has experienced the first ever outbreak of African swine fever (ASF). The first known cases occurred exclusively in wild boar in forest areas in Brandenburg and Saxony; in July 2021, infected domestic pigs were also confirmed for the first time. As wild boar are considered the main reservoir for the virus in the European region, an effective interruption of this infection chain is essential. In particular, the removal and safe disposal of infected carcasses and the direct disinfection of contaminated, unpaved ground are priorities in this regard. For the disinfection, highly potent as well as environmentally compatible disinfectants must be used, which are neither influenced in their effectiveness by the soil condition nor by increased organic contamination. Thus, in this study, slaked lime, milk of lime and quicklime (1% to 10% solutions) were selected for efficacy testing against the test virus recommended by the German Veterinary Society (DVG), Modified Vaccinia Ankara virus (MVAV), and ASF virus (ASFV) in conjunction with six different forest soils from Saxony in two different soil layers (top soil and mineral soil) each. In summary, 10% of any tested lime type is able to inactivate both MVAV and ASFV under conditions of high organic load and independent of the water content of the soil. At least a 4 log reduction of the virus titer in all tested forest soil types and layers and by all applied lime types was observed. In conclusion, the high efficacy and suitability of all tested lime products against both viruses and in the presence of high organic load in forest soil can be confirmed and will help to control ASF spread.